2015
DOI: 10.2466/15.pms.121c26x0
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's Disease Patients with Dominant Hemibody Affected by the Disease Rely More on Vision to Maintain Upright Postural Control

Abstract: This study assesses the association between disease onset side (dominant or non-dominant) and vision on postural control of Parkinson's disease patients. Patient volunteers composed two groups, according to the onset side affected: Dominant group (n=9; M age=66.1 yr., SD=7.2; 6 women, 3 men) and Non-dominant group (n=9; M age=67.4 yr., SD=6.4; 6 women, 3 men). The groups' postural control was assessed by posturography during quiet upright stance in two conditions, Eyes open and Eyes closed. Two-way analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Integration of visual sensory information is essential for appropriate movement initiation and execution. Inferior temporal lobe dysfunction may influence motor function and daily activities through impaired processing of visual information (37,42). How does aberrant brain activity of this zone affect motor function in LPD patients needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integration of visual sensory information is essential for appropriate movement initiation and execution. Inferior temporal lobe dysfunction may influence motor function and daily activities through impaired processing of visual information (37,42). How does aberrant brain activity of this zone affect motor function in LPD patients needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that the left inferior temporal lobe is critical for semantic integration and visual processing ( 40 , 41 ). Lahr et al ( 42 ) have demonstrated that PD patients relied on visual input to maintain upright postural control. Integration of visual sensory information is essential for appropriate movement initiation and execution.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the PD population, limited research supports that FP measures may identify balance impairments, even in early disease stages, and may detect balance decline with disease progression [3235]. Rossi-Izquierdo et al [36] found that the SOT and LOS test differentiated between PD and healthy groups and between fallers from nonfallers within the PD cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Lahr et al [6], for example, showed that PD subjects presented a higher reliance on vision on the dominant side to compensate somatosensory system impairments. Vibrotactile neurofeedback, known to stimulate the proprioception of the subjects, has been proven beneficial to subjects with PD [7].…”
Section: Introductionmentioning
confidence: 99%